2021
DOI: 10.1039/d1qm00784j
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic frameworks towards bio-medical applications

Abstract: This mini review summarises the progress in the field of MOFs and their use in biomedical applications, from their early discovery and conception, to more recent achievements including promising in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 154 publications
0
39
0
Order By: Relevance
“…For example, the use of inorganic nanocrystals as nanocarriers for drug delivery presents various interesting specificities. Inorganic nanocarriers such as mesoporous silica [68], metal-organic framework [69,70] nanocrystals such as calcium phosphate, gold, iron oxide and quantum dots, have been studied for drug delivery [71,72]. They may have better stability against biodegradation than organic nanocarriers and may enable a more favorable biodistribution for drugs.…”
Section: Inorganic Nanocrystals As Therapeutic Enhancersmentioning
confidence: 99%
“…For example, the use of inorganic nanocrystals as nanocarriers for drug delivery presents various interesting specificities. Inorganic nanocarriers such as mesoporous silica [68], metal-organic framework [69,70] nanocrystals such as calcium phosphate, gold, iron oxide and quantum dots, have been studied for drug delivery [71,72]. They may have better stability against biodegradation than organic nanocarriers and may enable a more favorable biodistribution for drugs.…”
Section: Inorganic Nanocrystals As Therapeutic Enhancersmentioning
confidence: 99%
“…16,17 Combined with recent advances in nanoparticle synthesis, MOFs have shown great promise in a number of applications ranging from catalysis to biomedicine. [18][19][20] First reports of nanoMOFs as radioenhancers were published in 2018 when the Lin group used hafnium-based SBUs to synthesize high-Z nanoMOFs. By comparing two Hf-MOFs that differ in their SBU, they not only showed that the SBU choice influences the X-ray absorption efficiency but also confirmed that a larger surface area leads to increased ROS production.…”
Section: Introductionmentioning
confidence: 99%
“…Porous organic materials, such as metal‐organic frameworks (MOFs), porous polymers, or porous carbonaceous materials are an emerging class of functional nanostructures with unusual properties, which found applications in storage, catalysis, electronic and proton conductivity, [153] as sensors [154] or for molecular separation, [155] as well as in biomedical applications [156] . Structural parameters of the pores are adaptable in many ways by variation of pore volume, topology, surface area, resulting from the modifications of their chemical composition [157] .…”
Section: Photochromic Materials Triggered With Visible Lightmentioning
confidence: 99%